Hepatotoxicity of Statins as Determined by Serum Alanine Aminotransferase in a Pediatric Cohort With Dyslipidemia. Issue 2 (February 2019) - Desai, Nirav K.; Mendelson, Michael M.; Baker, Annette; Ryan, Heather H.; Griggs, Suzanne; Boghani, Meera; Yellen, Elizabeth; Buckley, Lucy; Gillman, Matthew W.; Zachariah, Justin P.; Graham, Dionne; Jonas, Maureen M.; et al.
ABSTRACT: Objective: The aim of the study was to evaluate the hepatotoxicity of statins, as determined by serum alanine aminotransferase (ALT), in children and adolescents with dyslipidemia in real-world clinical practice. Study design: Clinical and laboratory data were prospectively collected between September 2010 and March 2014. We compared ALT levels between patients prescribed versus not prescribed 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase inhibitors (statins), and then compared ALT before and after initiation of statins. Results: Over the 3.5-year observation period, there were 2704 ALT measurements among 943 patients. The mean age was 14 years; 54% were boys, 47% obese, and 208 patients were treated with statins. Median follow-up after first ALT was 18 months. The mean (SD) ALT in statin and non-statin users was 23 (20) U/L and 28 (28) U/L, respectively. In models adjusted for age, sex, and race, ALT was 2.1 U/L (95% CI 0.1 to 4.4; P = 0.04) lower among statin users, which was attenuated after adjustment for weight category. Patients started on statins during the observation period did not demonstrate an increase in ALT over time (ALT 0.9 U/L [95% confidence interval −5.2 to 3.4] increase per year; P = 0.7). Conclusions: In our study population, we did not observe a higher burden of ALT elevations among pediatric patients on statins as compared to those with dyslipidemia who are not on statins, supporting the hepatic safety of statin use in childhood. Abstract : Supplemental Digital Content is available in the text